PERBEDAAN BERAT BADAN LAHIR DAN NILAI APGAR BAYI PADA IBU PARITAS TINGGI DAN PARITAS RENDAH DI RSUD CILACAP TAHUN 2016 - Lestari, Yogi Andhi; ., Sohimah; Apriani, Evy (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Infant Mortality Rate in Indonesia is still the highest in ASEAN, this means showing the health status of Indonesian people is still low. One factor contributing to infant mortality is maternal factors such as social economy, education, age and parity. Parity is a very influential factor on the results of conception. Pregnancy of more than four children may result in, among other things, low birth weight, less nutrition, slower growth. To know the difference between Birth Weight and Infant Birth Rate on low parity mother with high parity mother at RSUD Cilacap 2016. Comparative descriptive research design with Cross Sectional time approach. The sample in this study was 1530 with details of 1340 low parity mothers and 190 high parity mothers. There was a significant difference of Birth Weight Born in low parity mother with high parity mother (p = 0,002). There was a significant difference between the Apgar Score of low parity mothers and high parity mothers (p = 0.014). Keywords: Birth Weight, APGAR Score, Parity